High frequency of pauses during intermittent locomotion of small South American gymnophthalmid lizards (Squamata, Gymnophthalmidae) - Höfling, Elizabeth; Renous, Sabine (Phyllomedusa: Journal of Herpetology, 2004)
We studied the locomotor behavior of two closely-related species of Gymnophthalmini lizards, Vanzosaura rubricauda and Procellosaurinus tetradactylus, that was imaged under laboratory conditions at a rate of 250 frames/s with a high-speed video camera (MotionScope PCI 1000) on four different substrates with increasing degrees of roughness (smooth perspex, cardboard, glued sand, and glued gravel). Vanzosaura rubricauda and P. tetradactylus are both characterized by intermittent locomotion, with pauses occurring with high frequency and having a short duration (from 1/10 to 1/3 s), and taking place in rhythmic locomotion in an organized fashion during all types of gaits and on different substrates. The observed variations in duration and frequency of pauses suggest that in V. rubricauda mean pause duration is shorter and pause frequency is higher than in P. tetradactylus. The intermittent locomotion observed in V. rubricauda and P. tetradactylus imaging at 250 frames/s is probably of interest for neurobiologists. In the review of possible determinants, the phylogenetic relationships among the species of the tribe Gymnophthalmini are focused.